Ariel Barrios Medina (coord.), Bernardo Alberto Houssay. Primer Premio Nobel Científico Argentino, Buenos Aires, Compact Disk, 1997. - Buch, Alfonso (Universidad Nacional de Quilmes, 1998)
Fil: Buch, Alfonso. Universidad Nacional de Quilmes. Centro de Estudios e Investigaciones; Argentina.